No Europe without Europa (KULT_online, 2012)
This anthology of 34 articles is partly based on the conference "Mythos Europa. Vom Stier zum Sternenkranz" (The Myth of Europa/e: From the Bull to the Circle of Golden Stars) at the University of Greifswald in December 2001 and brings together for the first time perspectives from different disciplines on the antique myth of the abduction of Europa by Zeus. Prominent representatives of a wide range of academic fields – from history and literary studies to philosophy and art history, ethnology and political science – and from European and non-European countries alike give a deep insight into the various possibilities of interpretation offered by the myth of Europa throughout history. In an informative manner readers are initiated inEuropean cultural heritage, which clearly includes the myth of the ancient princess Europa.